The complete guide to accelerating sales force performance - Zoltners, Andris A. (AMACOM, 2001)
Every firm's sales force combines the distinctive personalities of its members with the complex issues of size, pay structure, incentives, performance evaluation, and effective uses of new technology. And while underrepresented in most marketing texts, the success of the sales force is a major component in the overall success of most companies. The Complete Guide to Accelerating Sales Force Performance develops an effective, innovative framework for evaluating and improving the performance of any sales force. This book identifies and describes the key factors for creating a fast-track, go-to-market strategy. It's loaded with proven ideas for improving such "success drivers" as: culture sales force structure hiring sales manager selection training compensation technology sales territory design goal setting performance management. Packed with valuable insights and real-life examples, this guide is an excellent source of practical ideas for sales and marketing managers in all industries